2022
DOI: 10.1071/rd21161
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mononuclear immune cells during bovine pregnancy

Abstract: This study aimed to determine the differences in gene expression between mononuclear cells derived from peripheral blood and endometrium during pregnancy in cattle and to determine the proportion of mononuclear cells in the endometrium of pregnant and diestrous cows. Endometrial tissue and peripheral blood were collected from Day 34 ± 2 pregnant cows, and mononuclear cell populations were quantified and sorted (n = 5). The relative mRNA levels of inflammatory mediators was assessed by quantitative real time po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Monitoring biochemical indicators in the blood of cows throughout various stages of pregnancy can provide valuable insights into their health status and reproductive performance. Some essential biochemical indicators that are commonly assessed during different periods of cow pregnancy (Alhussien et al, 2018;Rutigliano et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Monitoring biochemical indicators in the blood of cows throughout various stages of pregnancy can provide valuable insights into their health status and reproductive performance. Some essential biochemical indicators that are commonly assessed during different periods of cow pregnancy (Alhussien et al, 2018;Rutigliano et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, progesterone plays a critical role in fertility, particularly in establishing and maintaining pregnancy. Studies with beef heifers and dairy cows have shown positive connections between higher concentrations of progesterone and improved immune functions immediately after conception (Velázquez et al, 2019;Leppo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of the anti-inflammatory cytokines, IL10, interleukin 4 (IL4), TGFB, and the enzyme IDO1 was also greater in blood leukocytes of pregnant versus cyclic cows (Yang et al, 2016; Mohapatra et al, 2020). The authors also observed that transcript abundance for interleukin 1 (IL1), interleukin 6 (IL6), interleukin 8 (IL8) and IL10 were greater in the endometrium compared with peripheral blood mononuclear cells (PBMC) (Rutigliano et al, 2022). Clearly, the establishment of pregnancy involves regulation of immune cell types to direct migration, proliferation, apoptosis, and cytokine secretion in the uterus and circulation.…”
Section: Introductionmentioning
confidence: 98%